Question
upstudy study bank question image url

Jika sisa pembagian polinomial \( p(x)=x^{3}+a x^{2}- \) \( 4 x+b \) oleh \( \left(x^{2}-3 x+2\right) \) adalah \( (9 x-5) \), hitunglah nilai \( 3 a-2 b \). A. 6 B. 2 C. -2 D. -4 E. -6

Ask by Reese Savage. in Indonesia
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The value of \( 3a - 2b \) is -4.

Solution

We are given the polynomial p(x) = x³ + a·x² - 4x + b and that when dividing it by (x² - 3x + 2), the remainder is (9x - 5). Since (x² - 3x + 2) factors as (x - 1)(x - 2), by the Remainder Theorem we have:   p(1) = 9·1 - 5 = 4   (1)   p(2) = 9·2 - 5 = 13   (2) Now, compute p(1) and p(2) in terms of a and b. 1. For x = 1:   p(1) = 1³ + a·1² - 4·1 + b = 1 + a - 4 + b = a + b - 3. Setting this equal to 4 gives:   a + b - 3 = 4 ⟹ a + b = 7.   (3) 2. For x = 2:   p(2) = 2³ + a·2² - 4·2 + b = 8 + 4a - 8 + b = 4a + b. Setting this equal to 13 gives:   4a + b = 13.   (4) Subtract equation (3) from equation (4):   (4a + b) - (a + b) = 13 - 7,   4a - a = 6,   3a = 6 ⟹ a = 2. Substitute a = 2 into equation (3):   2 + b = 7 ⟹ b = 5. Lastly, the problem asks for the value of 3a - 2b:   3(2) - 2(5) = 6 - 10 = -4. Therefore, the answer is -4.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Untuk menyelesaikan masalah ini, kita akan menggunakan Teorema Sisa dari Pembagian Polinomial. Kita tahu bahwa \( p(x) \) dibagi oleh \( (x^{2}-3x+2) \) dan menghasilkan sisa \( (9x-5) \). Karena \( x^{2}-3x+2 = (x-1)(x-2) \), kita dapat menghitung nilai p(1) dan p(2). Pertama, kita substitusi \( x = 1 \) ke dalam \( p(x) \): \[ p(1) = 1^{3} + a(1^{2}) - 4(1) + b = 1 + a - 4 + b = a + b - 3 \] Sisa untuk \( x = 1 \) juga dapat dicari dari \( 9(1) - 5 = 4 \). Jadi: \[ a + b - 3 = 4 \implies a + b = 7 \quad (1) \] Kemudian, substitusi \( x = 2 \): \[ p(2) = 2^{3} + a(2^{2}) - 4(2) + b = 8 + 4a - 8 + b = 4a + b \] Sisa untuk \( x = 2 \) adalah \( 9(2) - 5 = 13 \). Maka: \[ 4a + b = 13 \quad (2) \] Sekarang kita memiliki dua persamaan dari (1) dan (2): 1. \( a + b = 7 \) 2. \( 4a + b = 13 \) Kita bisa mengurangi persamaan (1) dari (2): \[ (4a + b) - (a + b) = 13 - 7 \] \[ 3a = 6 \implies a = 2 \] Sekarang substitusi nilai \( a \) ke dalam (1): \[ 2 + b = 7 \implies b = 5 \] Akhirnya, hitung \( 3a - 2b \): \[ 3(2) - 2(5) = 6 - 10 = -4 \] Jadi, nilai \( 3a - 2b \) adalah \( -4 \), maka jawabannya adalah D. -4.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy